Mengembangkan Aktivitas Belajar, Kreativitas, Dan Motorik Halus Menggunakan Model Project Based Learning Dengan Metode Demonstrasi - Nur Amalina Arifah; Aslamiah (Jurnal Pendidikan Sosial Dan Konseling, 2025)
The problem in this study is the low activity of children, children's creativity in fine motor skills activities, this is due to the lack of interesting activities that stimulate children. Efforts to solve this problem are using the Project Based Learning Model with the Demonstration Method. The purpose of the study is to describe teacher activities, children's activities, creativity and analyze fine motor development. The approach used is a qualitative approach with the type of Classroom Action Research (CAR). The setting of this study was group A1 of Putra II Banjarmasin Kindergarten with 20 children. Data collection used observation techniques, assessment of teacher activities, children's activities, and results of fine motor development. The findings showed that teacher activity reached very good criteria at meeting 4. Children's activity reached 100% with very active criteria at meeting 4. Children's creativity reached 100% with very creative criteria at meeting 4. And the results of fine motor development reached 100% with BSB interpretation at meeting 4. It is recommended for head teachers, principals and further researchers to be one alternative when choosing an overall learning model.